Analisis Pengaruh Dinamisme Lingkungan dan Faktor Manajerial Terhadap Perencanaan Strategis dalam Upaya Meningkatkan Kinerja Organisasi Non-Profit dengan Pendekatan Balanced Scorecard - Siti Khusnul Rifani; Tengku Ezni Balqiah (Journal of Economics and Business Aseanomics (JEBA), 2021)
External environment changes and managerial factors are important to be considered in the preparation of strategic planning. Strategic planning is very important for the organization, not only for profit organizations but also for nonprofit organizations because a formal strategic planning can guide them to assess how far their goals have been achieved and how to achieve them. This study discusses how the dynamism of the external environment and managerial factors influence strategic planning and its implications for WWF Indonesia's performance using the Balanced Scorecard approach. The research method used is to use a survey of employees at WWF Indonesia and processed with SmartPLS 3.0. The results show that external business environment dynamism and managerial factors can influence strategic planning which ultimately affects the improvement of WWF Indonesia's performance.